Relating alkaline stability to the structure of quaternary phosphonium cations. Issue 47 (25th July 2018) - Zhang, Bingzi; Long, Hai; Kaspar, Robert B.; Wang, Junhua; Gu, Shuang; Zhuang, Zhongbin; Pivovar, Bryan; Yan, Yushan
Abstract : A semi-empirical formula based on the Taft equation is established to directly estimate alkaline stability of quaternary phosphonium (QP) cations from the 31 P NMR chemical shift δ and the steric substituent constant E s . Abstract : Alkali-stable quaternary phosphonium (QP) is a type of cationic group for hydroxide exchange membranes (HEMs). To elucidate the relationship between structure and alkaline stability, we investigated the kinetics and degradation mechanism of a series of QP cations by both experiment and computation, and established a semi-empirical formula based on the Taft equation to directly estimate alkaline stability of QP cations from the 31 P NMR chemical shift δ and the steric substituent constant E s, facilitating the search for QP cations with improved alkaline stability.